Combined effect of the solar activity and ENSO on the tropical cyclone genesis frequency in the southeastern part of the western North Pacific - Li, Shuang; Li, Zhangqun; Ling, Sining (Frontiers in Earth Science, 2023)
This study analyzes the frequency characteristics of tropical cyclone (TC) genesis in the southeastern part of western North Pacific (SEWNP) during June–November from 1965 to 2019 and investigates the possible combined effect of the solar activity and El Niño-Southern Oscillation (ENSO). Results suggest that TCs generated in the SEWNP have the longest lifetime and greatest strength, and its frequency has apparent interannual and decadal variations, which is jointly affected by the solar activity and ENSO. In El Niño years during declining phases of solar cycle (1–3 years following the solar maximum), positive TC genesis frequency anomalies in the SEWNP are significantly strong and tend to occur in extreme anomalies. While the opposite is true for La Niña during ascending phases of solar cycle (1–3 years following the solar minimum). However, there exists no significant feature in the combined effect of La Niña (El Niño) and declining (ascending) phases of solar cycle. When declining (ascending) phases of solar cycle and El Niño (La Niña) are combined, the overlapping effect leads to apparently warmer (colder) sea surface temperature (SST) anomalies in the central equatorial Pacific and colder (warmer) SST anomalies in the western Pacific, so the SST gradient anomalies are stronger. It enhances low-level westerly (easterly) wind anomalies and upper-level easterly (westerly) wind anomalies, which is favorable for the further decrease (increase) of the vertical wind shear in the eastern (most) part of SEWNP. Moreover, the stronger and more westerly low-level convergence (divergence) center appears in the Pacific, causing stronger low-level convergent (divergent) flow and upper-level divergent (convergent) flow anomalies, and strengthened (suppressed) ascending movement anomalies in the SEWNP. As a result, the TC genesis frequency in the SEWNP is much higher (lower). Further diagnoses show that absolute vorticity plays a leading role in El Niño years during declining phases of solar cycle, and its contribution is obviously much greater than other environmental factors. It is not perfectly symmetrical in La Niña years during ascending phases of solar cycle when the contribution of absolute vorticity is the greatest, but vertical wind shear is also important.